Higher Education for forcibly displaced migrants in Turkey. Issue 3 (3rd April 2023) - Kondakci, Yasar; Zayim Kurtay, Merve; Kaya Kasikci, Sevgi; Senay, Hanife Hilal; Kulakoglu, Busra
ABSTRACT: Higher education (HE) provides a unique opportunity to accomplish social and economic integration and mitigate the impact of displacement for forcibly displaced migrants (FDMs) in the long run. Against this backdrop, the purpose of the study is to explore the HE experiences of Syrian FDMs in Turkey. Utilizing snowball sampling, 24 FDMs in Turkey were interviewed. The results suggested that for the FDMs, HE was a mechanism for reconstructing their lives. However, they faced several challenges before and after access to HE. These challenges emanated from the education system itself due to the difficulties in accessing official documents from the home country, managing the admission process of different universities and language barriers as well as the broader social, economic, and cultural systems (e.g., public pushback). Concerning the challenges rooted in its education system, Turkey exhibited a dynamic approach to dealing with the problems and opening space for Syrian FDMs in HE. However, the challenges resulting from discrimination cause Syrian FDMs to question their sense of belonging stemming from cultural, geographical, and religious proximity to Turkey and reexamine their intentions of staying in Turkey forever.